'This is the last episode': the association between problematic binge‐watching and loneliness, emotion regulation, and sleep‐related factors in poor sleepers. (17th October 2022) - Alfonsi, Valentina; Varallo, Giorgia; Scarpelli, Serena; Gorgoni, Maurizio; Filosa, Maria; De Gennaro, Luigi; Musetti, Alessandro; Franceschini, Christian
Summary: Evidence on the relation between binge‐watching and sleep quality is still scarce and inconsistent and none has taken into account both the healthy and pathological dimensions of the phenomenon. This study aimed at filling this gap by investigating both aspects in healthy participants with high and low sleep quality. Further, we aimed at identifying sociodemographic, psychological and sleep‐related determinants of problematic binge‐watching in poor sleepers. We first conducted independent comparisons between good ( n  = 253) and poor sleepers ( n  = 209) on different binge‐watching symptoms and motives, assessed through 'Binge‐watching Engagement and Symptoms' and 'Watching TV Series Motives' questionnaires, respectively. Then, we focused on the problematic aspects of binge‐watching in poor sleepers, investigating the role of emotion regulation, loneliness, and sleep‐related factors using hierarchical multiple regressions. Comparisons between the two groups revealed a greater extent of binge‐watching behaviour ( t  = −2.80, p  = 0.005) and greater use of this practise to cope with negative emotions ( t  = −4.17, p  < 0.001) in poor sleepers. In addition, hierarchical multiple regressions showed that gender (β = −0.166, p  = 0.008), alcohol consumption (β = −0.135, p  = 0.035), emotional dysregulation (β = 0.260, p  = 0.001; β = 0.298, p < 0.001), feelings of loneliness (β = 0.159, p  = 0.029; β = 0.199, p  = 0.003), and daytime sleepiness (β = 0.149, p  = 0.016) are significant determinants of problematic binge‐watching in this population. In addition to showing for the first time the relationship between sleep quality and different aspects of binge‐watching, our findings indicate that emotional dysregulation, feelings of loneliness, and daytime sleepiness play a key role in determining problematic binge‐watching in poor sleepers, possibly due to the existence of a pathological vicious circle between these factors in poor sleepers.